A Solution to the Paradox of Analysis. (17th March 2016) - Balaguer, Mark; Horgan, Terry
Abstract: The paradox of analysis asks how a putative conceptual analysis can be both true and informative. If it is true then isn't it analytic? And if it is analytic then how can it be informative? Our proposed solution rests on a distinction between explicit knowledge of meaning and implicit knowledge of meaning and on a correlative distinction between two kinds of conceptual competence (which we call platonistic competence and application competence). If one initially possesses only implicit knowledge of the meaning of a given concept and the associated linguistic expression, then a conceptual analysis can be both analytic and informative.